The minimum wage from a two-sided perspective - Brown, Alessio J.G.; Merkl, Christian; Snower, Dennis J. (Kiel, 2014)
"This paper sheds new light on the effects of the minimum wage on employment from a two-sided theoretical perspective, in which firms' job offer and workers' job acceptance decisions are disentangled. Minimum wages reduce job offer incentives and increase job acceptance incentives. We show that sufficiently low minimum wages may do no harm to employment, since their job-offer disincentives are countervailed by their job-acceptance incentives."